Republic of South Sudan : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; Statement by the Executive Director for the Republic of South Sudan. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
After five years of civil conflict, the warring parties came to a peace agreement in September 2018. Until the COVID-19 crisis broke out, improved political stability and an uptick in international oil prices led to significant progress, with a rebound in economic growth, a decline in inflation, and a stabilization of the exchange rate. The COVID-19 pandemic is severely disrupting South Sudan's economy, leading to a sharp decline in projected growth (-3.6 percent in FY20/21, about 10 percentage points below the pre-pandemic baseline) and a contraction of oil export proceeds-the main source of exports and fiscal revenue-which has given rise to urgent balance of payments needs and opened a large fiscal financing gap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet